Investasi Dalam Kacamata Islam - Subroto Subroto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to analyze the concept of investment in the Islamic perspective and the principles that distinguish it from conventional investment. The method used is qualitative with a normative-descriptive approach, through a literature review of Islamic law, fatwas from scholars, and sharia investment regulations. The results show that investment in Islam must be based on the principles of fairness, transparency, and freedom from the elements of usury, uncertainty, and chance. Investment instruments that are sharia-compliant include sharia stocks, sukuk, and mudharabah, which emphasize the fair distribution of risk and profit. This study emphasizes that sharia-based investment is not only oriented towards financial gain, but also pays attention to the ethical aspects and the interests of the community, thus creating a more stable and equitable economic system.